Knowledge, attitude and practices of secondary school teachers regarding school health services in children - Chavan, Girish Manohar; Chavan, Vishwajeet Manohar (International Journal Of Community Medicine And Public Health, 2018)
Background: Being an essential member of school, it is the responsibility of teachers to inculcate healthy habits amongst children which thereby makes the future generation of a country healthy. Objective of the study was to assess knowledge, attitude and practices of school teachers and compare them between urban and rural school teachers with special reference to school health services. Methods: The present cross-sectional study was carried out in 520 rural teachers and 185 urban teachers with an aim of assessing teacher’s health related knowledge and skills. Results: Of the rural school teachers, 10.38% received school health training as compared to only 7.57% urban teachers. First aid training was received by 84 rural in contrast to only 24 urban school teachers. Mean percent knowledge score was similar for rural and urban school teachers. Mean percent attitude score amongst all schools, irrespective of their location, was 90%. Mean percent practice score among rural school teachers was 86.67% as compared to 76.67% among urban school teachers. Teacher performance score (sum of knowledge, attitude, and practices towards school health) in rural teachers was 79.64%, while that in urban school teachers was 72.21%. Conclusions: School teachers should be periodically assessed at various levels to get status of their knowledge and understanding regarding health education. It should be ensured that teachers should receive continued education and trainings related to health, especially importance of first aid and hygiene.